Electrostatic complementarity in an aldose reductase complex from ultra-high-resolution crystallography and first-principles calculations - Muzet, Nicolas (National Academy of Sciences, 2003)
The electron density and electrostatic potential in an aldose reductase holoenzyme complex have been studied by density functional theory (DFT) and diffraction methods. Aldose reductase is involved in the reduction of glucose in the polyol pathway by using NADPH as a cofactor. The ultra-high resolution of the diffraction data and the low thermal-displacement parameters of the structure allow accurate atomic positions and an experimental charge density analysis. Based on the x-ray structural data, order-N DFT calculations have been performed on subsets of up to 711 atoms in the active site of the molecule. The charge density refinement of the protein was performed with the program mopro by using the transferability principle and our database of charge density parameters built from crystallographic analyses of peptides and amino acids. Electrostatic potentials calculated from the charge density database, the preliminary experimental electron density analysis, DFT computations, and atomic charges taken from the amber software dictionary are compared. The electrostatic complementarity between the cofactor NADP(+) and the active site shows up clearly. The anchoring of the inhibitor is due mainly to hydrophobic forces and to only two polar interaction sites within the enzyme cavity. The potentials calculated by x-ray and DFT techniques agree reasonably well. At the present stage of the refinement, the potentials obtained directly from the database are in excellent agreement with the experimental ones. In addition, these results demonstrate the significant contribution of electron lone pairs and of atomic polarization effects to the host and guest mechanism.